2010
DOI: 10.1002/pd.2627
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk of pre‐eclampsia between 11 and 13 weeks' gestation by combining maternal characteristics and serum analytes, PAPP‐A and free β‐hCG

Abstract: Objective To determine if a simplified model for predicting pre-eclampsia can be developed by combining first trimester serum analytes, PAPP-A and free β-hCG, and maternal characteristics. Methods A retrospective cohort study of patients seen for first-trimester aneuploidy screening from 2003–2009. The 5th, 10th, 90th and 95th percentiles for the analyte-MoMs for our population were determined and evaluated for association with pre-eclampsia. Univariate and backward stepwise logistic regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 17 publications
2
71
0
1
Order By: Relevance
“…Consistent with this, previous studies observed that risk stratification based on multiple of the median (MoM) values of serum β-hCG levels might be advantageous in high-risk pregnancies, especially noting that a high MoM of β-hCG levels is observed in patients with PE compared to normal pregnant women [16,17]. In contrast, several other studies could not verify this association between β-hCG levels and PE [18,19]. Therefore, we performed a meta-analysis to assess the potential value of MoM of β-hCG serum levels in predicting PE pathology.…”
Section: Introductionsupporting
confidence: 42%
“…Consistent with this, previous studies observed that risk stratification based on multiple of the median (MoM) values of serum β-hCG levels might be advantageous in high-risk pregnancies, especially noting that a high MoM of β-hCG levels is observed in patients with PE compared to normal pregnant women [16,17]. In contrast, several other studies could not verify this association between β-hCG levels and PE [18,19]. Therefore, we performed a meta-analysis to assess the potential value of MoM of β-hCG serum levels in predicting PE pathology.…”
Section: Introductionsupporting
confidence: 42%
“…Using single biochemical markers usually has a low predictive value in the first trimester. PAPP-A, a glycoprotein synthesized in the placenta, has been shown to be a powerful predictive biochemical marker of PE when combined with Doppler ultrasound, reaching 70% sensitivity at 95% specificity (Spencer et al, 2008;Goetzinger et al, 2010;Anderson et al, 2011). However, some recent studies evaluating PAPP-A as a firsttrimester predictive marker for PE showed conflicting results that indicated no differentiation between complicated and uncomplicated pregnancies (Mikat et al, 2011;Stirnemann et al, 2011).…”
mentioning
confidence: 95%
“…But the screening performance is extremely low when used as a single biochemical marker and the predictive rate is only about 10-20 % [14]. Several studies denoted low first or second trimester serum PAPP-A value is predictive and diagnostic biochemical marker of preeclampsia [14][15][16][17][18][19][20][21][22][23]. First trimester serum PAPP-A is low also prior to other pregnancy complications, such as in pregnancies developing fetal growth restriction, spontaneous miscarriage placental abruption, preterm birth and stillbirth and gestational diabetes [15,16,20,23].…”
Section: Pregnancy-associated Placental Protein Amentioning
confidence: 99%
“…PAPP-A has been evaluated as a predictive and diagnostic biochemical marker for PE. But the screening performance is extremely low when used as a single biochemical marker and the predictive rate is only about 10-20 % [14]. Several studies denoted low first or second trimester serum PAPP-A value is predictive and diagnostic biochemical marker of preeclampsia [14][15][16][17][18][19][20][21][22][23].…”
Section: Pregnancy-associated Placental Protein Amentioning
confidence: 99%